2016
DOI: 10.1007/s11162-016-9409-z
|View full text |Cite
|
Sign up to set email alerts
|

Life Happens (Outside of College): Non-College Life-Events and Students’ Likelihood of Graduation

Abstract: Students' lives outside of college can have dramatic effects on academic outcomes (e.g., grades, persistence, graduation). However, the manner in which students' lives outside of college are referenced in college-effects models suggests some uncertainty among scholars as to which, and how, student experiences outside of an institution affect college student outcomes. Using longitudinal data from a racially diverse sample of 3914 students (997 White, 1051 Black, 915 Hispanic, and 951 Asian) attending 28 institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…This result can be interpreted in two ways: Students who were less focused on nonacademic activities were more efficient in allocating time toward reading, and students who were more focused on nonacademic activities were less efficient in allocating time toward reading texts. Our findings are similar to those in other studies in suggesting a negative association between participation in nonacademic activities and performance, in this case reading (Lotkowski et al, 2004;Pascarella et al, 2004;Reason et al, 2016). Surprisingly, however, those who felt they "never" managed time well were more likely to believe they were doing the reading that they had been asked to do than those who felt they "always" managed time well.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result can be interpreted in two ways: Students who were less focused on nonacademic activities were more efficient in allocating time toward reading, and students who were more focused on nonacademic activities were less efficient in allocating time toward reading texts. Our findings are similar to those in other studies in suggesting a negative association between participation in nonacademic activities and performance, in this case reading (Lotkowski et al, 2004;Pascarella et al, 2004;Reason et al, 2016). Surprisingly, however, those who felt they "never" managed time well were more likely to believe they were doing the reading that they had been asked to do than those who felt they "always" managed time well.…”
Section: Discussionsupporting
confidence: 88%
“…An important resource in accomplishing self-regulation is self-rationing of time, yet unfortunately, some, including students, are known to struggle with self-regulation, goal setting, and identifying effective learning strategies (Bembenutty, 2001), which is another reason why there is a need to investigate whether students are efficient in selfrationing their time. Lotkowski et al (2004) found that nonacademic factors had the strongest positive impact on academic performance, yet a study by Cox et al (2016) found that nonuniversity life events had a negative impact on the graduation rates of students. In a study by Pascarella et al (2004), nonacademic activities, such as intercollegiate athletics and work experience, were found to have a significantly negative impact on the academic achievements of students.…”
Section: Time For Readingmentioning
confidence: 99%
“…More than half of college students experience at least one stressful life event during a single year of college (Cox, Reason, Nix, & Gillman, 2016). Stressful life events can trigger a variety of responses, with the development of post-traumatic stress (PTS) symptoms being a severe reaction on the stressresponse continuum (Long et al, 2008;Ruscio, Ruscio, & Keane, 2002).…”
mentioning
confidence: 99%
“…As can be seen, the estimates remain almost unchanged when applying both models. To ease interpretation, results reported in Table 2 are presented as oddsratios (whereby a ratio of less than 1 reflects a decreased likelihood of graduation) (Cox et al, 2016). From the above table, we can conclude that the likelihood of men leaving higher education studies is 1.42 times that of women.…”
Section: Other Characteristicsmentioning
confidence: 98%